THE EFFECT OF REGIONAL ORIGINAL REVENUE AND REMAINING BUDGET FINANCING ON LOCAL GOVERNMENT FINANCIAL PERFORMANCE OF PROVINCIAL LOCAL GOVERNMENTS NORTH SUMATRA FOR THE PERIOD 2018 - 2022 - Ginting, Mitha Christina; Simanjuntak, Arthur; Situmorang, Duma Rahel; Panjaitan, Rike Yolanda; Simanjuntak, Reymondo (Jurnal Ilmiah Accusi, 2024)
Regional Original Revenue is “all revenues received by the region obtained from various existing in the region, collected in accordance with applicable laws and regulations”. Remaining Budget Financing is “the difference between the realization of budget revenues and expenditures in one period. The purpose of this study was to test and analyze the effect of Local Original Revenue and Remaining Budget Financing on Local Government Financial Performance. The sample of this study was 33 districts / cities in North Sumatra province in 2018 - 2022 and obtained a total of 165 observation data. The sample technique used was saturated sample. According to the findings of this study, Local Revenue has a significant positive effect on Local Government Financial Performance, but Remaining Budget Financing has a significant negative impact. Simultaneously or together, Local Revenue and Budget Financing Surplus have a significant positive impact on Local Government Financial Performance. The two independent variables, Regional Original Revenue and Remaining Budget Financing, can account for 30.9% of the Local Government Financial Performance variable, with the remaining 69.1% explained by variables not included in the study